2011
DOI: 10.1080/19425120.2011.608592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Growth on Fecundity and Egg Quality of Wild and Captive Atka Mackerel

Abstract: Trade‐offs in energy allocation between growth and reproduction can result in variations in reproductive potential in fish with differing growth patterns. Spawning biomass is often used as a proxy for reproductive potential on the assumption that fecundity is directly proportional to body weight. We examined variations in the reproductive potential of Atka mackerel Pleurogrammus monopterygius by studying the effect of differential growth and condition patterns on fecundity, atresia, and egg energy. Fecundity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Cultured fish were longer, heavier and were more fecund than the wild fish. Similar results in other species have also shown cultured fish grew faster than the wild ones, such as western ruivaco Achondrostoma occidentale (Mameri et al, 2018), Atka mackerel Pleurogrammus monopterygius (McDermott et al, 2011), steelhead Oncorhynchus mykiss (Kostow, 2004), Atlantic salmon (Blanchet et al, 2008), gilthead sea bream Sparus aurata (Grigorakis et al, 2002) and brown trout (Hedenskog et al, 2002). O'Sullivan et al (2020) showed that the fecundity of cultured Atlantic salmon was approximately 1.4 times higher than wild ones.…”
Section: Discussionsupporting
confidence: 73%
“…Cultured fish were longer, heavier and were more fecund than the wild fish. Similar results in other species have also shown cultured fish grew faster than the wild ones, such as western ruivaco Achondrostoma occidentale (Mameri et al, 2018), Atka mackerel Pleurogrammus monopterygius (McDermott et al, 2011), steelhead Oncorhynchus mykiss (Kostow, 2004), Atlantic salmon (Blanchet et al, 2008), gilthead sea bream Sparus aurata (Grigorakis et al, 2002) and brown trout (Hedenskog et al, 2002). O'Sullivan et al (2020) showed that the fecundity of cultured Atlantic salmon was approximately 1.4 times higher than wild ones.…”
Section: Discussionsupporting
confidence: 73%
“…Many stock assessments studies neglect the share of stocked and wild fish in the population, which can create biases in the interpretation of the population parameters extracted for the whole metapopulation. For instance, a higher survival and cumulative dominance of stocked fish in the population could wrongly indicate an accelerated somatic growth rate and early maturation of fish in the population, given that fish in captivity often grow faster and mature earlier than wild individuals (McDermott et al, 2011;Zupa et al, 2017), which is not possible to see in this study due to the selection of wild fish with comparable sizes with the stocked individuals to avoid the bias of the presence of slower and much smaller fish in the wild group (van Densen and Vijverberg, 1982). This option allow us to compare individuals with more similar conditions, because the slow growing pikeperch are in fact much smaller than the fast growing individuals in the studied area (Jůza et al, 2013), but refrain us from assessing the full spectrum of otolith shapes in the wild population.…”
Section: Discussionmentioning
confidence: 99%
“…Las hembras de L. guttatus empiezan a madurar sus ovocitos en octubre y desovan entre noviembre y enero, reflejado en el aumento de individuos en los estadios III y IV. Posterior al desove los organismos se preparan para producir nuevas células reproductoras a partir de enero (estadios I y II), lo que coincide con lo que reportan Rojas (1996Rojas ( -1997 La fecundidad de los peces se relaciona con el proceso de vitelogénesis y con las variables morfométricas (McDermontt et al, 2011;Eraso et al, 2017), esto último se constata en el presente estudio, por la correlación positiva, débilmente significativa, entre el peso de los individuos y el peso de la gónada.…”
Section: Discussionunclassified